Contemporary State and Development Dynamics of Human Capital in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
In article the modern condition in the Republic of Kazakhstan and the dynamics of its development over a five year period (2008-2012). As a key summary indicator of development of the Kazakhstan population it is selected the human development index (HDI) calculated by experts of the Program of development of United Nations (UNDP) together with a group of independent international experts. The index measures the average achievements in a country in three basic dimensions of human development: a long and healthy life, access to knowledge and a decent standard of living. Along with the annual reports of UNDP, the information base of the research also made reference and statistical materials of the Agency of the Republic of Kazakhstan on statistics which gave the opportunity to describe fully the current situation in the RK the field of human capital.
Keywords: human capital; human development index; life expectancy; education; gross domestic product